Unique latitudinal shape of ion upper transition height (HT) surface during deep solar minimum (2008–2009). Issue 2 (16th February 2015) - Tulasi Ram, S.; Heelis, R.; Gowtam, V. Sai; Ajith, K. K.; Su, S.‐Y.
Abstract The ionospheric upper transition height (HT) is found to increase dramatically by ~100 km from 2008–2009 to 2010 only for a marginal increase in solar activity (F10.7) by 11.76 solar flux units. The latitudinal variation of HT surface during 2008–2009 period exhibits a local minimum at equatorial latitudes and increase at low latitudes. Further, the HT at equatorial latitudes exhibits slower rate of increase than at low latitudes. These interesting features are new and different from those reported in literature. A quick loss of O+ and increase in H+ ions are observed around ~550 to 650 km indicating that the charge exchange reaction is responsible for the slower rate of increase and lowered HT at equatorial latitudes. These new aspects of HT are more conspicuously observed during this deep solar minimum period where the resonant charge exchange reaction is taking place at altitudes as low as ~550 km.